2008
DOI: 10.1007/s11547-008-0352-8
|View full text |Cite
|
Sign up to set email alerts
|

Small animal imaging facility: new perspectives for the radiologist

Abstract: In recent years, new technologies have become available for imaging small animals. The use of animal models in basic and preclinical sciences, for example, offers the possibility of testing diagnostic markers and drugs, which is becoming crucial in the success and timeliness of research and is allowing a more efficient approach in defining study objectives and providing many advantages for both clinical research and the pharmaceutical industry. The use of these instruments offers data that are more predictive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 62 publications
(41 reference statements)
0
24
0
1
Order By: Relevance
“…However, one limitation of this method is that the activity of inflammatory processes can only be assessed by secondary characteristics by micro-CT, such as affection of adjacent strucutre or pleural effusion. Other imaging techniques such as magnetic resonance imaging (MRI), micro-positron emission tomography (PET) and optical imaging could provide functional data, with micro-PET beeing an especially promising candidate to robustly assess inflammatory activity by increase of glucose metabolism as detected by 18 F-fluoro-deoxyglucose micro-PET [17-19], which might be particularly relevant in terms of monitoring acute exacerbations of pulmonary fibrosis in small laboratory animals.…”
Section: Discussionmentioning
confidence: 99%
“…However, one limitation of this method is that the activity of inflammatory processes can only be assessed by secondary characteristics by micro-CT, such as affection of adjacent strucutre or pleural effusion. Other imaging techniques such as magnetic resonance imaging (MRI), micro-positron emission tomography (PET) and optical imaging could provide functional data, with micro-PET beeing an especially promising candidate to robustly assess inflammatory activity by increase of glucose metabolism as detected by 18 F-fluoro-deoxyglucose micro-PET [17-19], which might be particularly relevant in terms of monitoring acute exacerbations of pulmonary fibrosis in small laboratory animals.…”
Section: Discussionmentioning
confidence: 99%
“…La modalità di studio micro-RM, insieme ad altre metodiche di diagnostica per immagini per piccoli animali, stanno emergendo come tecniche chiave nell'imaging molecolare in vivo grazie alla possibilità di individuare eventi con suffi ciente sensibilità, specifi cità, risoluzione temporale e spaziale. L'imaging non invasivo su piccoli animali in vivo ha acquisito un ruolo sempre maggiore nella ricerca preclinica [16].…”
Section: Discussionunclassified
“…The micro-MRI study method and other diagnostic imaging techniques for small animals are emerging as key techniques in in vivo molecular imaging, given their ability to identify events with suffi cient sensitivity, specifi city and temporal and spatial resolution. Noninvasive, small-animal in vivo imaging has taken on a increasingly important role in preclinical research [16].…”
Section: Discussionmentioning
confidence: 99%
“…In MPS-VI humans, observations made during diagnostic imaging, surgery, and autopsy have shown that dural thickening at the cervical level can contribute to compressive myelopathy (2-5). Advances in medical imaging techniques have led to major improvements in evaluating dural thickness in humans (21,22).…”
Section: Response To Iv-ertmentioning
confidence: 99%